Design and Evaluation of an Application for Recording of Pharmacy Students' Attendance via Smartphones and Personal Computer - Maryam Aghakouchakzadeh; Mandana Izadpanah; Kaveh Eslami; Reza Ganji; Leila Kouti (Research Center for Rational Use of Drugs (RCRUD), 2017)
Background: Attendance management is one of the most important issues in the educational institutions. The traditional method for attendance recording is manually recording by professors in the school or university which is associated with several problems. We proposed the design and utilization of an electronic application for students' attendance recording via smartphones and PCs. Methods: This study was a cross-sectional and Quasi-experimental study, which held in the department of clinical pharmacy in the school of pharmacy in Ahvaz Jundishapur University of medical sciences. Group I was assigned to the manually recording of student attendance. Group II was assigned to the design and utilization of an electronic application for registration of attendance. Each of the professors records the students' attendance in the class by smartphones. Finally, the satisfaction of the professors about the application was assessed with the 6-item questionnaire. Also, the efficacy of the application was evaluated through the comparison of the number of recorded attendance and the number of absent recorded in group I and II. Results: The results of satisfaction survey illustrated that all of the professors found the electronic recording of the attendance was the more useful than the traditional method and lead to the reducing the possibility of errors, the time spent, and the pleasure of students. Also, the comparison between the numbers of students' recorded attendance and numbers of absence recorded were higher by utilization of the application more than by the traditional method. Conclusion: The students' attendance recording application can improve performance compared to the manually attendance management system via decreasing the possibility errors and continuous assessing during a semester.